Pembentukan Kepribadian Islami pada Anak Melalui Hadis: Studi Tematik Psikologi Perkembangan - Sri Mulyaningsih; Muhammad Alif; Hikmatul Luthfi (STAI Nurul Qadim, 2025)
The development of Islamic personality from an early age serves as a vital foundation in shaping a morally upright generation aligned with the spiritual and social values taught in Islam. In this context, the Hadiths of Prophet Muhammad (peace be upon him) function as ethical and moral guidelines that can be utilized to instill Islamic character in children. This study aims to examine the role of Hadiths in shaping children's personalities through the lens of developmental psychology. Employing a qualitative descriptive approach, this research is based on a literature review, drawing primarily from selected Hadith collections and scholarly works on child developmental psychology. Thematic analysis was conducted to identify Hadiths that convey core character values such as honesty, compassion, responsibility, and discipline. The findings reveal that the values embedded in Hadiths are highly relevant to the psychological stages of child development, particularly in the domains of moral and social growth. The internalization of these values can be effectively achieved through age-appropriate strategies, including modeling behavior, positive reinforcement, and effective communication within family and educational settings. The study concludes that integrating Islamic teachings from Hadith with developmental psychology approaches offers a comprehensive and effective strategy for cultivating an Islamic personality in children. Therefore, the active involvement of parents and educators is crucial in applying these values in the daily lives of children